Starting with Freud, again! Jacobs, M (1992) Sigmund Freud. London: Sage Publications. ISBN 0 8039 8465 0 (pbk), 150 pages. - Hayes, Grahame (PINS-Psychology in Society, 2026)
The psychological and psychoanalytic literature might appear to be saturated with introductions to Freud, and hence any new text in this area is simply going to be a wasteful repetition of its many predecessors. And while Jacobs’s text covers many familiar areas of Freud’s work, his approach is refreshingly contemporary, as well as invitingly written. The "re-reading" which certain of the introductory texts on Freud imply, assures a critical perspective towards psychoanalytic ideas. Psychoanalysis is not, nor should be, an orthodox theory of the unconscious: heterodoxy is axiomatic of psychoanalysis.